P653 The changing epidemiology of IBD in the western world: a population-based study from Denmark. (21st January 2022) - Agrawal, M; Christensen, H; Bøgsted, M; Colombel, J F; Jess, T; Allin, K
Abstract: Background: Mitigating the burden of inflammatory bowel disease (IBD) in Western countries requires understanding how its epidemiology is evolving. We conducted a temporal analysis of the epidemiology of IBD between 1995 and 2018 in the Danish nationwide cohort. Methods: We used the Danish Civil Registration System (CRS) to obtain demographic information on all residents in Denmark between January 1, 1995 and December 31, 2018. We obtained information on Crohn's disease (CD) and ulcerative colitis (UC) diagnosis from the National Patient Registry (NPR) using International Classification of Disease 8/10 codes. IBD diagnosis was defined as having at least two CD- or UC-related registrations within a two-year period and the date of the first IBD-related registration was considered as the date of diagnosis. We estimated overall and annual incidence rates and prevalence of CD and UC standardized with respect to age and sex. Results: 52, 407 individuals met the criteria for IBD diagnosis in the period 1995–2018, of which 17, 355 (33%) were diagnosed with CD and 35, 052 (67%) were diagnosed with UC. The median age at diagnosis (IQR) for CD and UC was 34 (22, 53) and 43 (29, 60) years, respectively. 9, 745 (56.2%) and 18, 332 (52.3%) individuals with CD and UC, respectively, were of female sex. During the study period, 1995–2018, the overall incidence rate (95% CI) rose from 9.2 (8.4, 10) per 100, 000 person years (PY) to 18 (16.8, 19) per 100, 000 PY for CD, corresponding to a 94.9% increase, and from 21.1 (19.9, 22.4) per 100, 000 PY to 28.4 (27, 29.8) per 100, 000 PY for UC, corresponding to a 34.1% increase. The incidence rates of CD and UC increased for all age groups, at different rates, highest for CD in age group 15–39 years (Figure). While CD incidence was consistently higher in women, increase in CD and UC incidence was comparable between both sexes. The prevalence of IBD also increased from 1995–2018 (225.6% and 218.4% for CD and UC, respectively) with the greatest increase in UC prevalence among individuals older than 40 years of age (248.4%). Conclusion: The epidemiology of IBD has shifted in the last 20 years with a still increasing incidence of CD and UC in young adults, and a sharply increased prevalence in older age groups, especially for UC. These findings have implications towards understanding environmental shifts associated with this evolution as well as preparing for management of an aging IBD population.